Measurement of Osteoporosis Using Quantitative Ultrasound Technique - Aya Al-Gorani; Mushtaq Al-Jubbori; khalid Majeed (College of Education for Pure Sciences, 2022)
The aim of study is to measure osteoporosis in the right foot at the heel (calcaneus) by using the quantitative ultrasound (QUS) technique. It was measured (SOS, BUA, BQI, T-score and Z-score). While the usage of the DXA technique is measure the tissue thickness. Osteoporosis represents low bone mineral density (BMD). The heel of the foot (calcaneus) uses in QUS measurements because it contains a high ratio of trabecular bone. T-score is the predominant the diagnosis of osteoporosis used for adults, men and women over 50 years. From T-score can be to know the ratio of BMD, according to the WHO a T-score can be classified (Normal, Osteopenia and Osteoporosis). Age group 31-40 years was T-score for both sex (-0.667) is meaning (Normal bone). In the age group, 51-60 years was T-score (-1.60) for both sex represents (osteopenia). While age group 71-80 years T-score for females (-2.56) and males (-3.30), means that both males and females have (osteoporosis). P-value